Novel Particle Engineering Techniques in Drug Delivery: Review of Coformulations Using Supercritical Fluids and Liquefied Gases (Hungarian Journal of Industry and Chemistry, 2004)
This paper aimed to survey the numerous publications and patents issued in the fields of supercritical fluid assisted and cryogenic formulation techniques with special regard to coformulations of active substrate – excipient composites. These methods open new possibilities in formulation of drug carrier composites with targeted physical properties including particle size, morphology, crystallinity, polymorphism and residual solvent content Both methods were proved to be viable alternatives to conventional formulation techniques.